Analysis of the transcriptional activity of model piggyBac transgenes stably integrated into different loci of the genome of CHO cells in the absence of selection pressure - L. A. Yarinich; A. A. Ogienko; A. V. Pindyurin; E. S. Omelina (Вавиловский журнал генетики и селекции)
CHO cells are most commonly used for the synthesis of recombinant proteins in biopharmaceutical production. When stable producer cell lines are obtained, the locus of transgene integration into the genome has a great influence on the level of its expression. Therefore, the identification of genomic loci ensuring a high level of protein production is very important. Here, we used the TRIP assay to study the influence of the local chromatin environment on the activity of transgenes in CHO cells. For this purpose, reporter constructs encoding eGFP under the control of four promoters were stably integrated into the genome of CHO cells using the piggyBac transposon. Each individual transgene contained a unique tag, a DNA barcode, and the resulting polyclonal cell population was cultured for almost a month without any selection. Next, using the high-throughput sequencing, genomic localizations of barcodes, as well as their abundances in the population and transcriptional activities were identified. In total, ~640 transgenes more or less evenly distributed across all chromosomes of CHO cells were characterized. More than half of the transgenes were completely silent. The most active transgenes were identified to be inserted in gene promoters and 5’ UTRs. Transgenes carrying Chinese hamster full-length promoter of the EF-1α gene showed the highest activity. Transgenes with a truncated version of the same promoter and with the mouse PGK gene promoter were on average 10 and 19 times less active, respectively. In total, combinations of genomic loci of CHO cells and transgene promoters that together provide different levels of transcriptional activity of the model reporter construct were described.